MAVS maintains mitochondrial homeostasis via autophagy - Sun, Xiaofeng (Cell Discov, 2016)
Mitochondrial antiviral signalling protein (MAVS) acts as a critical adaptor protein to transduce antiviral signalling by physically interacting with activated RIG-I and MDA5 receptors. MAVS executes its functions at the outer membrane of mitochondria to regulate downstream antiviral signalling, indicating that the mitochondria provides a functional platform for innate antiviral signalling transduction. However, little is known about whether and how MAVS-mediated antiviral signalling contributes to mitochondrial homeostasis. Here we show that the activation of MAVS is sufficient to induce autophagic signalling, which may mediate the turnover of the damaged mitochondria. Importantly, we find MAVS directly interacts with LC3 through its LC3-binding motif ‘YxxI’, suggesting that MAVS might act as an autophagy receptor to mediate mitochondrial turnover upon excessive activation of RLR signalling. Furthermore, we provide evidence that both MAVS self-aggregation and its interaction with TRAF2/6 proteins are important for MAVS-mediated mitochondrial turnover. Collectively, our findings suggest that MAVS acts as a potential receptor for mitochondria-associated autophagic signalling to maintain mitochondrial homeostasis.